Kajian Etnobotani Dalam Upacara Ngaruwat Bumi Di Kampung Adat Banceuy Desa Sanca Kecamatan Ciater Kabupaten Subang, Jawa Barat - Indrianita D M Nur Azizah; Tri Cahyanto (International Forum of Researchers and Lecturers, 2024)
The people of the Banceuy traditional village, Sanca Village, Ciater District, Subang Regency have a unique tradition of expressing gratitude for natural products, especially rice (Oryza sativa), which has been carried out since the time of their ancestors and is known as the Ngaruwat Bumi ceremony. Ngaruwat Bumi is a traditional ceremony that is routinely held every year at the end of the month of Rayagung. This research aims to analyze ethnobotanical studies on the Ngaruwat Bumi ceremony in the Banceuy Indigenous village community. The research was carried out in three stages, namely literature study, interviews, and data processing and analysis. The data taken is primary data and secondary data. Primary data is data obtained directly in the field through interviews with respondents. Meanwhile, secondary data is data obtained from previously existing research or publications. Sampling used a purposive random sampling method with 15 respondents. The research results showed that six types of plants were used in the Ngaruwat traditional ceremonies carried out by the people of the Banceuy traditional village, namely Oryza sativa, Arenga pinnata, Cocos nucifera, Cordyline fruticosa, Coleus scutellarioides, Justicia gendarussa, and Musa paradisiaca.